Tuberculosis in renal transplant recipients: experience in a kidney transplant unit in Peru - Méndez Chacon, Pedro (2016)
Introduction. Organ transplantation carries a risk of contracting tuberculosis (TB) due to the required concurrent immunosuppression. Literature reports an incidence of 0.35%-15%. There is no data on this matter in our region. Objectives. To determine epidemiology, clinical findings and prognosis of TB in renal transplantation recipients in an endemic area. The study also aimed to analyze multidrugresistant (MDR) cases. Design. Retrospective study. Setting. Department of Nephrology, Hospital Edgardo Rebagliati Martins, EsSalud, Lima, Peru. Material. Clinical charts of renal transplant patients attended during 1999-2014. Interventions. Onset of tuberculosis was determined in 619 cases of renal transplant, as well as analysis of multidrug-resistant cases. Main outcome measures. Installation of tuberculosis and cases of multidrug resistance. Results. TB developed in 22 patients (3.5%), more prevalent that the country general population (96/100 000/year). Fever (57%) and chronic cough (28%) were the most common symptoms. Extrapulmonary TB (50%) predominated over pulmonary (40%) and disseminated TB (10%). TB occurred usually after one year (72%) and on average within the 41st month post transplantation. Seven cases (28%) presented creatinine above 2 mg% at diagnosis and three of them returned to dialysis. There were four cases of MDR TB. Conclusions. Early diagnosis based on TB clinical suspicion and timely treatment improves the prognosis in this population of immunosuppressed patients.